Incidental postmortem diagnosis of DIPNECH in a patient with previously unexplained ‘asthma bronchiale’ - Stenzinger, Albrecht; Weichert, Wilko; Hensel, Mario; Bruns, Holger; Dietel, Manfred; Erbersdobler, Andreas (Pathology, research and practice, 2010)
We report the case of a 69-year-old female patient with a progressively worsening, clinically unexplained symptomatic asthma bronchiale who eventually died due to urosepsis. A subsequent autopsy revealed diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH), a very rare preneoplastic disease of the pulmonary neuroendocrine cell system, as the cause of asthma bronchiale in our patient. We hypothesize that DIPNECH may be an underestimated cause of obstructive lung disease in a certain subset of patients. Therefore, studies are warranted to obtain statistically reliable demographic and clinical data of this pulmonary condition. Moreover, this case strongly argues for the relevance and significance of non-forensic autopsies in the clinical setting.